Ecosystems on ice: The microbial ecology of Markham Ice Shelf in the high Arctic - Vincent, W.F. (Warwick F.); Mueller, D. (Derek); Bonilla, S. (Sylvia) (Cryobiology, 2004)
Microbial communities occur throughout the cryosphere in a diverse range of ice-dominated habitats including snow, sea ice, glaciers, permafrost, and ice clouds. In each of these environments, organisms must be capable of surviving freeze-thaw cycles, persistent low temperatures for growth, extremes of solar radiation, and prolonged dormancy. These constraints may have been especially important during global cooling events in the past, including the Precambrian glaciations. One analogue of these early Earth conditions is the thick, landfast sea ice that occurs today at certain locations in the Arctic and Antarctic. These ice shelves contain liquid water for a brief period each summer, and support luxuriant microbial mat communities. Our recent studies of these mats on the Markham Ice Shelf (Canadian high Arctic) by high performance liquid chromatography (HPLC) showed that they contain high concentrations of chlorophylls a and b, and several carotenoids notably lutein, echinenone and β-carotene. The largest peaks in the HPLC chromatograms were two UV-screening compounds known to be produced by cyanobacteria, scytonemin, and its decomposition product scytonemin-red. Microscopic analyses of the mats showed that they were dominated by the chlorophyte genera cf. Chlorosarcinopsis, Pleurastrum, Palmellopsis, and Bracteococcus, and cyanobacteria of the genera Nostoc, Phormidium, Leptolyngbya, and Gloeocapsa. From point transects and localized sampling we estimated a total standing stock on this ice shelf of up to 11,200 tonnes of organic matter. These observations underscore the ability of microbial communities to flourish despite the severe constraints imposed by the cryo-ecosystem environment.